Aesthetic Judging as Interface: Getting to Know What You Experience - Onerva Kiianlinna; Joonas Kurjenmiekka (ESPES, 2023)
One of the aims of Aesthetics is to understand aesthetic experience, that of our own and that of others. Yet, the underlying question of how we can get information about other people’s aesthetic experience has not been granted enough attention. This article contributes to bridging this gap. The main argument is that by resorting to aesthetic judging, we can get information about other people’s aesthetic experience without sharing it. This article outlines how aesthetic judging works as an interface to aesthetic experience. Aesthetic judging allows us to access aesthetic experience indirectly: with it, we can get some information about aesthetic experience. Aesthetic judging thus positions us in relation to someone else’s aesthetic experience. In a nutshell, learning about aesthetic experience happens via aesthetic judging in at least three ways proposed and analyzed here: “aesthetic participation”, “affective appropriation”, and “distanced aesthetic empathy”.